Pemanfaatan Media Audio Visual Situs Purbakala Pugung Raharjo sebagai Media Belajar Sejarah bagi Mahasiswa Pendidikan Sejarah STKIP PGRI Bandar Lampung - Febrianti, Aurora Nandia; Muhammad, Ulul Azmi; Suryati, Wawat (Jurnal Ilmiah Dikdaya, 2022)
The purpose of this study was to determine the use of audio-visual media at the Pugung Raharjo Archaeological site as a medium for learning history for students of history education at STKIP PGRI Bandar Lampung. The research method used in this research is using a descriptive qualitative approach. Data collection techniques used in this research are literature study, observation, interview, and documentation techniques. The data validity technique uses triangulation of data sources and for data analysis using data reduction, data presentation, and drawing conclusions. The Pugung Raharjo Archaeological Site is one of the historical heritages in Lampung. This site is not only used for historical tourism visits, this site is also used as a source of learning local history for students of history education study programs. In the current digital 4.0 era, various learning media are used to support success in learning activities, one of which is using audio-visual media. The results showed that the use of audio-visual media for the Pugung Raharjo Archaeological Site as a medium for learning history was well received by students.